Pain relief following a single‐dose intra‐articular injection of methylprednisolone in the temporomandibular joint arthralgia—A multicentre randomised controlled trial. (10th October 2018) - Isacsson, Göran; Schumann, Mohamad; Nohlert, Eva; Mejersjö, Christina; Tegelberg, Åke
Summary: Background: Temporomandibular joint (TMJ) arthralgia is a painful condition assumed to be associated with local inflammation. Objective: The objective of the present study was to determine the efficacy for reducing pain of a single‐dose intra‐articular (IA) injection of methylprednisolone to the TMJ. The hypothesis was that methylprednisolone would effectively reduce TMJ pain. Methods: This randomised, double‐blind, parallel‐group, multicentre, controlled study included visits for enrolment, treatment and 4‐week follow‐up. The study included patients 18 years and older who had been diagnosed with unilateral TMJ arthralgia. All participants were randomly assigned to receive 1 mL IA injections of methylprednisolone or saline. The primary outcome was change in recorded pain intensity on a visual analogue scale (VAS) at maximum jaw opening, analysed in the per protocol population. Results: In total, 54 patients were randomly assigned to single‐dose IA injections with methylprednisolone (n = 27) or saline (n = 27). Between baseline and the 4‐week follow‐up, VAS‐rated pain intensity at maximum jaw opening decreased from a mean of 61.0 (95% confidence interval [CI]: 50.1; 70.7) to 33.9 (95% CI: 21.6; 46.2) in the methylprednisolone group and from 59.6 (95% CI: 50.7; 65.9) to 33.9 (95% CI: 23.8; 43.9) in the saline group. The between‐group difference was not significant ( P = 0.812). Treatment‐related adverse events were doubled in the methylprednisolone group. Conclusion: Methylprednisolone provided no additional benefit for reducing pain, but caused more harm compared with saline following a single‐dose IA injection in patients with TMJ arthralgia.